Alone! alone! : lives of some outsider women - Dinnage, Rosemary (New York : New York Review Books, 2004)
"In the course of over thirty years of writing about psychology, child development, biography, and fiction, Rosemary Dinnage has encountered a variety of outstanding women, all of whom, in one way or another, felt powerfully alone." "Here she brings together her reflections on some of the most memorable of them." "Some of these women knew isolation through their dedication to duty, and others through their immersion in writing, painting, or politics. Some juggled with fantasy worlds in which they could end up stranded. Others learned the fine art of survival, fighting illness, hard childhoods, or a hostile public. All of them, whether trying to construct a life or a work of art - or both - suggest ways in which women can choose, learn, laugh, invent, dare, and of course wholeheartedly love or hate.".
"These women make up a gallery of the famous, the infamous, the once famous, and the never famous. In telling their stories, Rosemary Dinnage considers what aloneness may really be, how it begins, how it feels, and, above all, how this experience can teach and illuminate as well as hurt."--BOOK JACKET.
1. Amorous and proud : Gwen John -- 2. Black sequins and seaweed : Stevie Smith -- 3. Vicarage passions : Barbara Pym -- 4. Feeding on light : Simone Weil -- 5. Silenced : Nadia -- 6. Holding the baby : Clementine Churchill -- 7. Echoes : Ottoline Morrell -- 8. Flag bearer : Dora Russell -- 9. La Strepponi : Giuseppina Verdi -- 10. Famishment : Stosslova, Abba -- 11. Sheltering : Olive Schreiner -- 12. Scallywag & Co. : Blavatsky and Besant -- 13. Is it real? : Ruth -- 14. Benign spells : witches -- 15. Soppists and sapphists : Brazil and Blyton -- 16. Down to work : prostitutes -- 17. Innocent, unstoppable : Marie Stopes -- 18. Eadie or Eddie? : Patrick White -- 19. Satan laughed : Isak Dinesen -- 20. Almost queenly : Rebecca West -- 21. Great space and tundra : Slater, Jamison, Millett, France, Ferguson -- 22. Conspicuous gallantry : Margaret Oliphant -- 23. Her own straitjacket : Alice James -- 24. An ice-cold wreath : Katherine Mansfield.
Keywords: Women -- Biography; Women authors -- Biography